Preparation method of modified iron oxyhydroxide loaded polyamide nanofiltration membrane

Through the preparation method of polyamide nanofiltration membrane with modified iron hydroxyoxide load, the problems of low water flux, low interception rate and easy selection layer fall off are solved, and higher water flux and interception rate are achieved. Enhanced membrane stability.

CN119406253AActive Publication Date: 2025-02-11HEILONGJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411904125.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-02-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing nanofiltration membranes have problems such as low water flux, low interception rate and easy shedding of the selected layer.

Method used

By preparing a modified iron hydroxyoxide-loaded polyamide nanofiltration membrane, functionalized by silane coupling agent and polyethyleneimine-modified iron hydroxyoxide as the base film, a scaffold was formed to prevent the polyamide layer from being blocked and grafted Polyethyleneimine increases stability and crosslinking.

Benefits of technology

The water flux and retention rate of the nanofiltration membrane are improved, the selection layer is prevented from falling off, and the stability and acid resistance of the membrane are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406253A_ABST
    Figure CN119406253A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified iron oxyhydroxide loaded polyamide nanofiltration membrane, and belongs to the technical field of nanofiltration membranes. The problems that an existing nanofiltration membrane is low in water flux and interception rate, and a selection layer is prone to falling off are solved. The method comprises the following steps: preparing hydroxyl ferric oxide functionalized by a silane coupling agent; preparing polyethyleneimine modified iron oxyhydroxide; preparing a modified FeOOH base membrane; and preparing the modified FeOOH nanofiltration membrane. The nanofiltration membrane has higher water flux and rejection rate, the introduced modified iron oxyhydroxide is loaded on the base membrane to form a support, a polyamide layer is effectively prevented from entering the base membrane and blocking channels of the base membrane, and the modified iron oxyhydroxide has a large number of hydrophilic groups and can adsorb more water-phase monomers, so that the reaction of subsequent interfacial polymerization is facilitated, and the water flux and rejection rate of the nanofiltration membrane are improved. Meanwhile, the grafted polyethyleneimine has a large number of amino groups and can react with acyl chloride groups, so that the stability is improved, the selective layer is prevented from falling off, the crosslinking degree of the polyamide layer is increased, and a thinner and denser polyamide layer is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanofiltration membranes, and in particular relates to a method for preparing a polyamide nanofiltration membrane loaded with modified ferric oxyhydroxide. Background Art

[0002] The growth of the world's population, the improvement of living standards, the change in consumption patterns and the expansion of agricultural irrigation are the main driving forces for the increasing global demand for water. At present, the world's freshwater resources can meet the growing demand, but the distribution of water resources varies greatly in time and space, resulting in water shortages in some areas at specific times. Nanofiltration membrane technology is a new technology that uses external pressure or chemical potential difference to make the solvent pass through a semipermeable membrane to separate solutes and solvents. It has the advantages of simple process, high integration, low cost and automatic operation. It has been widely used in many fields, including drinking water treatment, sewage treatment, seawater desalination, wastewater reuse, etc., to ensure water quality safety, treat water pollution, improve water environment and alleviate water resource crisis. Provide technical support.

[0003] At present, the most common method for preparing nanofiltration membranes is to use microfiltration membranes or ultrafiltration membranes as base membranes, and to form polyamide nanofiltration membranes on them through the interfacial polymerization reaction of piperazine and tricarboxylic acid chloride. The performance optimization methods of nanofiltration membranes mainly include water channel design, roughness optimization, hydrophilicity optimization, thickness optimization, etc. For example, micron-sized nanomaterials can be used as an intermediate layer to regulate the performance of nanofiltration membranes. Iron oxyhydroxide materials have the advantages of low cost, simple preparation, stable structure, and environmental protection. Iron oxyhydroxide has a long strip morphology and can be used as a bracket between the base layer and the selection layer. It can effectively reduce the blockage of the base membrane by the polyamide layer. However, as the content of iron oxyhydroxide increases, the force between the selection layer and the base membrane decreases, resulting in the problem of easy detachment of the selection layer. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of low water flux, low interception rate and easy shedding of the selective layer in the existing nanofiltration membrane, and to provide a method for preparing a modified ferric oxyhydroxide-loaded polyamide nanofiltration membrane.

[0005] A method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane is carried out according to the following steps:

[0006] 1. Preparation of iron oxyhydroxide functionalized with silane coupling agent:

[0007] 0.5 g of oxyhydroxide was added to 50 ml of ethanol aqueous solution, and then magnetically stirred after ultrasonic dispersion. Then 1 mL of silane coupling agent was added and reacted at 40° C. for 2 h. After centrifugation, washing and drying, silane coupling agent-functionalized oxyhydroxide was obtained.

[0008] 2. Preparation of polyethyleneimine-modified iron oxyhydroxide:

[0009] 0.2 g of the silane coupling agent functionalized iron oxyhydroxide was added to 50 mL of anhydrous methanol, and then ultrasonically dispersed and magnetically stirred. Then 2 g of polyethyleneimine was added, and the temperature was raised to 90° C., refluxed for 6 h, and naturally cooled to room temperature. After centrifugation, washing and drying, polyethyleneimine-modified iron oxyhydroxide was obtained, which was recorded as FeOOH / PEI.

[0010] 3. Preparation of modified iron oxyhydroxide-based membrane:

[0011] 3.0 mg of the above FeOOH / PEI was added to 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a modified FeOOH suspension, and then the suspension was filtered from 0 mL to 10 mL through a PES bottom membrane with a diameter of 4.0 cm, and after drying and washing, a modified FeOOH base membrane was obtained;

[0012] 4. Preparation of modified FeOOH nanofiltration membrane:

[0013] In a fume hood, the modified FeOOH-based membrane is horizontally spread on a glass plate with a smooth surface, and then a membrane frame is placed opposite to the center of the modified FeOOH-based membrane, and the four sides are fixed with iron clips; a piperazine (PIP) aqueous solution is poured into the membrane frame, and the remaining solution in the membrane frame is poured out and drained after 90 seconds, and after drying for 10 to 20 minutes, a trimesoyl chloride (TMC)-n-hexane solution is poured in, and the remaining solution in the membrane frame is poured out after 40 seconds, and then 5 mL of n-hexane solution is poured in and shaken for 30 seconds, and then the glass plate is vertically dried until the membrane surface is completely dry, the iron clip is removed and the membrane frame is taken down, and the membrane is removed from the glass plate with tweezers and marked, and then placed in a forced air drying oven, and thermally cross-linked at 60° C. for 30 minutes to obtain a modified oxyhydroxide-loaded polyamide nanofiltration membrane, thereby completing the preparation method.

[0014] Furthermore, the synthesis of the oxyhydroxide described in step 1: 2.16 g of FeCl3·6H2O and 20 mL of ethylenediamine were added to 40 ml of deionized water, stirred for 20 min, transferred and sealed in a high-temperature reaction kettle, kept at 85°C for 12 h, then cooled to room temperature, centrifuged and washed, and vacuum dried at 80°C to obtain oxyhydroxide.

[0015] Furthermore, the aqueous solution of ethanol in step 1 is prepared by mixing 45 mL of deionized water and 5 mL of anhydrous ethanol.

[0016] Furthermore, the magnetic stirring after ultrasonic dispersion in step 1 is: ultrasonic dispersion for 30 minutes and then magnetic stirring for 30 minutes.

[0017] Furthermore, the silane coupling agent in step 1 is: KH560.

[0018] Furthermore, the centrifugation, washing and drying in step 1 are performed by centrifugation at a speed of 4000 r / min for 5 min, followed by washing with anhydrous ethanol for 2 to 3 times, and then vacuum drying at 40° C. for 24 h.

[0019] Furthermore, the magnetic stirring after the ultrasonic dispersion in step 2: ultrasonic dispersion for 10 minutes and magnetic stirring for 30 minutes.

[0020] Furthermore, the centrifugation, washing and drying in step 2 are performed by centrifuging at a speed of 4000 r / min for 5 minutes, then washing with deionized water and anhydrous methanol for 2 to 3 times respectively, and then drying at 60° C. for 24 hours.

[0021] Furthermore, the drying and washing in step 3: drying in an oven at 60° C. for 3 minutes, and then rinsing with deionized water 2 to 3 times.

[0022] Furthermore, the amount of the piperazine aqueous solution in step 4 is 5 mL, and the concentration is 0.5% / wv.

[0023] Furthermore, the amount of the trimesoyl chloride-n-hexane solution in step 4 is 5 mL, and the concentration is 0.1% / wv.

[0024] The modified ferric hydroxide loaded polyamide nanofiltration membrane prepared in the present invention has higher water flux and retention rate than general polyamide nanofiltration membranes. This is because the introduced modified ferric hydroxide is loaded on the base membrane to form a scaffold, which can effectively prevent the polyamide layer generated by interfacial polymerization from entering the base membrane and blocking the base membrane pores. In addition, the modified ferric hydroxide has a large number of hydrophilic groups, which can adsorb more aqueous phase monomers and help the subsequent interfacial polymerization reaction. At the same time, the grafted polyethyleneimine has a large number of amino groups, which can react with acyl chloride groups to increase stability and prevent the selective layer from falling off. In addition, the amino groups can consume the acyl chloride groups on the surface more quickly, increase the cross-linking degree of the polyamide layer, and form a thinner and denser polyamide layer.

[0025] The invention is suitable for the preparation of a polyamide nanofiltration membrane loaded with modified ferric oxyhydroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the SEM image of FeOOH / PEI in Example 1;

[0027] Figure 2 The infrared spectra of FeOOH / KH560, FeOOH / PEI and existing FeOOH in Example 1 are shown;

[0028] Figure 3The infrared spectra of the PES base membrane, the FeOOH / PEI polyamide nanofiltration membrane in Example 1 and the unmodified polyamide nanofiltration membrane in the comparative example;

[0029] Figure 4 Surface, cross-sectional SEM and AFM images of the PES base membrane, the modified FeOOH base membrane in Example 1, the FeOOH / PEI polyamide nanofiltration membrane and the unmodified polyamide nanofiltration membrane in the comparative example; wherein Figure a and Figure b are surface SEM images of the PES base membrane and the modified FeOOH base membrane, respectively; Figure c and Figure d are surface SEM images of the unmodified polyamide nanofiltration membrane and the FeOOH / PEI polyamide nanofiltration membrane, respectively; Figure e and Figure f are cross-sectional SEM images of the unmodified polyamide nanofiltration membrane and the FeOOH / PEI polyamide nanofiltration membrane; Figure g and Figure h are AFM images of the unmodified polyamide nanofiltration membrane and the FeOOH / PEI polyamide nanofiltration membrane;

[0030] Figure 5 The first figure is the water contact angle diagram of the surface of the unmodified polyamide membrane; the second figure is the water contact angle diagram of the polyamide membrane after adding FeOOH / PEI;

[0031] Figure 6 It is the molecular weight cut-off diagram of FeOOH / PEI polyamide nanofiltration membrane and unmodified polyamide nanofiltration membrane;

[0032] Figure 7 The water flux and rejection rate diagram of FeOOH / PEI polyamide nanofiltration membrane with different loading amounts;

[0033] Figure 8 This is the effect of different material concentrations on the performance of FeOOH / PEI polyamide nanofiltration membrane;

[0034] Fig. 9 This is the long-term operation diagram of FeOOH / PEI polyamide nanofiltration membrane;

[0035] Fig.10 This is a diagram showing the effect of acid-resistant treatment on FeOOH / PEI polyamide nanofiltration membrane. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0037] Specific implementation method 1: This implementation method is a method for preparing a polyamide nanofiltration membrane loaded with modified ferric oxyhydroxide, which is carried out according to the following steps:

[0038] 1. Preparation of iron oxyhydroxide functionalized with silane coupling agent:

[0039] 0.5 g of oxyhydroxide was added to 50 ml of ethanol aqueous solution, and then magnetically stirred after ultrasonic dispersion. Then 1 mL of silane coupling agent was added and reacted at 40° C. for 2 h. After centrifugation, washing and drying, silane coupling agent-functionalized oxyhydroxide was obtained.

[0040] 2. Preparation of polyethyleneimine-modified iron oxyhydroxide:

[0041] 0.2 g of the silane coupling agent functionalized iron oxyhydroxide was added to 50 mL of anhydrous methanol, and then ultrasonically dispersed and magnetically stirred. Then 2 g of polyethyleneimine was added, and the temperature was raised to 90° C., refluxed for 6 h, and naturally cooled to room temperature. After centrifugation, washing and drying, polyethyleneimine-modified iron oxyhydroxide was obtained, which was recorded as FeOOH / PEI.

[0042] 3. Preparation of modified iron oxyhydroxide-based membrane:

[0043] 3.0 mg of the above FeOOH / PEI was added to 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a modified FeOOH suspension, and then the suspension was filtered from 0 mL to 10 mL through a PES bottom membrane with a diameter of 4.0 cm, and after drying and washing, a modified FeOOH base membrane was obtained;

[0044] 4. Preparation of modified FeOOH nanofiltration membrane:

[0045] In a fume hood, the modified FeOOH-based membrane is horizontally spread on a glass plate with a smooth surface, and then a membrane frame is placed opposite to the center of the modified FeOOH-based membrane, and the four sides are fixed with iron clips; a piperazine (PIP) aqueous solution is poured into the membrane frame, and the remaining solution in the membrane frame is poured out and drained after 90 seconds, and after drying for 10 to 20 minutes, a trimesoyl chloride (TMC)-n-hexane solution is poured in, and the remaining solution in the membrane frame is poured out after 40 seconds, and then 5 mL of n-hexane solution is poured in and shaken for 30 seconds, and then the glass plate is vertically dried until the membrane surface is completely dry, the iron clip is removed and the membrane frame is taken down, and the membrane is removed from the glass plate with tweezers and marked, and then placed in a forced air drying oven, and thermally cross-linked at 60° C. for 30 minutes to obtain a modified oxyhydroxide-loaded polyamide nanofiltration membrane, thereby completing the preparation method.

[0046] The polyethyleneimine in step 2 of this embodiment is: PEI, M=10000.

[0047] The film frame in step 4 of this embodiment is an organic solvent-resistant film frame.

[0048] The 90 seconds described in step 4 of this embodiment: The purpose of the 90-second waiting time is to allow the aqueous solution to infiltrate the surface of the modified FeOOH-based membrane.

[0049] The 40 seconds mentioned in step 4 of this embodiment: the purpose of the 40 seconds of waiting time is to allow PIP and TMC to fully react.

[0050] The purpose of pouring 5 mL of n-hexane solution in step 4 of this embodiment is to wash away the unreacted trimesoyl chloride monomer on the membrane surface and accelerate the volatilization of the membrane surface.

[0051] The polyamide nanofiltration membrane loaded with modified iron oxyhydroxide obtained in step 4 of this embodiment is placed in a sealed bag and stored at room temperature for later use.

[0052] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that, in step 1, the synthesis of ferric oxyhydroxide is as follows: 2.16 g of FeCl3·6H2O and 20 mL of ethylenediamine are added to 40 ml of deionized water, stirred for 20 min, transferred and sealed in a high-temperature reaction kettle, kept at 85° C. for 12 h, then cooled to room temperature, centrifuged and washed, and vacuum dried at 80° C. to obtain ferric oxyhydroxide. The other steps and parameters are the same as those in specific embodiment 1.

[0053] In this embodiment, the washing is performed by rinsing with deionized water 2 to 3 times, the purpose of which is to eliminate residual chloride ions.

[0054] Specific implementation method 3: This implementation method is different from specific implementation method 2 in that the ethanol aqueous solution in step 1 is prepared by mixing 45 mL of deionized water and 5 mL of anhydrous ethanol. The other steps and parameters are the same as those in specific implementation method 2.

[0055] Specific embodiment 4: This embodiment is different from specific embodiment 1 in that the magnetic stirring after ultrasonic dispersion in step 1 is: ultrasonic dispersion for 30 minutes and magnetic stirring for 30 minutes. Other steps and parameters are the same as those in specific embodiment 1.

[0056] Specific implementation method 5: This implementation method is different from the specific implementation method 1 in that the silane coupling agent in step 1 is KH560. The other steps and parameters are the same as those in the specific implementation method 1.

[0057] Specific embodiment 6: This embodiment is different from specific embodiment 1 in that the centrifugation, washing and drying in step 1 are: centrifugation at a speed of 4000 r / min for 5 minutes, followed by washing with anhydrous ethanol for 2 to 3 times, and then vacuum drying at 40°C for 24 hours. The other steps and parameters are the same as those in specific embodiment 1.

[0058] Specific embodiment 7: This embodiment is different from specific embodiment 1 in that the magnetic stirring after ultrasonic dispersion in step 2: ultrasonic dispersion for 10 minutes and magnetic stirring for 30 minutes. Other steps and parameters are the same as those in specific embodiment 1.

[0059] Specific embodiment eight: This embodiment differs from specific embodiment one in that the centrifugation, washing and drying in step two are: centrifugation at a speed of 4000 r / min for 5 min, followed by washing with deionized water and anhydrous methanol for 2 to 3 times, and then drying at 60° C. for 24 h. The other steps and parameters are the same as those in specific embodiment one.

[0060] Specific embodiment 9: This embodiment differs from specific embodiment 1 in that the drying and washing in step 3 are: drying in a 60°C oven for 3 minutes, and then rinsing with deionized water 2 to 3 times. Other steps and parameters are the same as those in specific embodiment 1.

[0061] Specific embodiment 10: This embodiment differs from specific embodiment 1 in that the amount of piperazine aqueous solution used in step 4 is 5 mL, and the concentration is 0.5% / wv. Other steps and parameters are the same as those in specific embodiment 1.

[0062] Specific implementation eleven: This implementation differs from specific implementation one in that the amount of trimesoyl chloride-n-hexane solution used in step four is 5 mL, and the concentration is 0.1% / wv. Other steps and parameters are the same as those in specific implementation one.

[0063] The beneficial effects of the present invention are verified by the following examples:

[0064] Embodiment 1:

[0065] A method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane is carried out according to the following steps:

[0066] 1. Preparation of iron oxyhydroxide functionalized with silane coupling agent:

[0067] 0.5 g of ferric oxyhydroxide was added to 50 ml of ethanol aqueous solution, and then magnetically stirred after ultrasonic dispersion. Then 1 mL of KH560 was added and reacted at 40 °C for 2 h. After centrifugation, washing and drying, KH560-functionalized ferric oxyhydroxide (FeOOH / KH560) was obtained.

[0068] 2. Preparation of polyethyleneimine-modified iron oxyhydroxide:

[0069] 0.2 g of the above FeOOH / KH560 was added to 50 mL of anhydrous methanol, and then magnetically stirred after ultrasonic dispersion. Then 2 g of polyethyleneimine was added, and the temperature was raised to 90° C., refluxed for 6 h, and naturally cooled to room temperature. After centrifugation, washing and drying, polyethyleneimine-modified iron oxide was obtained, which was recorded as FeOOH / PEI.

[0070] 3. Preparation of modified iron oxyhydroxide-based membrane:

[0071] 3.0 mg of the above FeOOH / PEI was added to 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a modified FeOOH suspension, and then the suspension was filtered from 0 mL to 10 mL through a PES bottom membrane with a diameter of 4.0 cm, and after drying and washing, a modified FeOOH base membrane was obtained;

[0072] 4. Preparation of modified FeOOH nanofiltration membrane:

[0073] In a fume hood, the modified FeOOH-based membrane is horizontally spread on a glass plate with a smooth surface, and then a membrane frame is placed directly opposite to the center of the modified FeOOH-based membrane, and the four sides are fixed with iron clips; a piperazine (PIP) aqueous solution is poured into the membrane frame, and the remaining solution in the membrane frame is poured out and drained after 90 seconds, and after drying for 10 to 20 minutes, a trimesoyl chloride (TMC)-n-hexane solution is poured in, and the remaining solution in the membrane frame is poured out after 40 seconds, and then 5 mL of n-hexane solution is poured in and shaken for 30 seconds, and then the glass plate is vertically dried until the membrane surface is completely dry, the iron clip is removed and the membrane frame is taken down, and the membrane is removed from the glass plate with tweezers and marked, and then placed in a blast drying oven, and thermally cross-linked at 60° C. for 30 minutes to obtain a modified oxyhydroxide-loaded polyamide nanofiltration membrane (referred to as FeOOH / PEI polyamide nanofiltration membrane), and the preparation method is completed;

[0074] Synthesis of ferric oxyhydroxide in step 1 of this embodiment: 2.16 g of FeCl3·6H2O and 20 mL of ethylenediamine were added to 40 ml of deionized water, stirred for 20 min, transferred and sealed in a high-temperature reaction kettle, kept at 85°C for 12 h, then cooled to room temperature, centrifuged and washed, and vacuum dried at 80°C to obtain ferric oxyhydroxide;

[0075] The aqueous solution of ethanol in step 1 is prepared by mixing 45 mL of deionized water and 5 mL of anhydrous ethanol;

[0076] The magnetic stirring after ultrasonic dispersion in step 1 is: ultrasonic dispersion for 30 minutes and then magnetic stirring for 30 minutes;

[0077] Centrifugation, washing and drying in step 1: centrifugation at 4000 r / min for 5 min, then washing with anhydrous ethanol for 3 times, and then vacuum drying at 40°C for 24 h;

[0078] The magnetic stirring after ultrasonic dispersion in step 2: ultrasonic dispersion for 10 minutes and magnetic stirring for 30 minutes;

[0079] Centrifugation, washing and drying in step 2: centrifugation at 4000 r / min for 5 min, then washing with deionized water and anhydrous methanol for 3 times each, and then drying at 60° C. for 24 h;

[0080] Drying and washing in step 3: drying in a 60°C oven for 3 min, and then rinsing with deionized water 3 times;

[0081] The amount of the piperazine aqueous solution in step 4 is 5 mL, and the concentration is 0.5% / wv;

[0082] The amount of trimesoyl chloride-n-hexane solution used in step 4 is 5 mL, and the concentration is 0.1% / wv.

[0083] Comparative Example:

[0084] In this example, the modified FeOOH base membrane is replaced with an unmodified PES base membrane, and then the method of step 4 of Example 1 is used for preparation to obtain an unmodified polyamide nanofiltration membrane.

[0085] result:

[0086] Figure 1 This is a SEM image of FeOOH / PEI obtained in step 2 of Example 1. Figure 1 As shown, FeOOH / PEI is a nanorod with a length of 440 nm and a width of 63 nm, which can be used as a scaffold.

[0087] Figure 2 The infrared spectra of FeOOH / KH560 obtained in step 1 of Example 1, FeOOH / PEI obtained in step 2, and existing FeOOH are shown in FIG. Figure 2 As shown, the peaks at 899cm-1 and 801cm-1 are caused by the bending vibration of Fe-OH in FeOOH, and the peak at 620cm-1 corresponds to the stretching vibration peak of Fe-O, confirming the successful synthesis of FeOOH. After reacting with KH560, the new peaks at 2925cm-1 and 2854cm-1 correspond to the stretching vibration peaks of CH in methyl and methylene, respectively, and the peak at 1112cm-1 corresponds to the stretching vibration peak of Si-O; proving that KH560 has been successfully grafted on the surface of FeOOH. After the introduction of PEI, 1658cm-1, 1476cm-1 and 1115cm-1 correspond to the stretching vibration peaks of -NH2, CH bending vibration and CN, respectively, indicating that PEI has been successfully grafted on the surface of FeOOH.

[0088] Figure 3 The infrared spectra of the PES base membrane, the FeOOH / PEI polyamide nanofiltration membrane in Example 1 and the unmodified polyamide nanofiltration membrane in the comparative example are shown in FIG. Figure 3 As shown in the figure, compared with the PES-based membrane, the FeOOH / PEI polyamide nanofiltration membrane and the unmodified polyamide nanofiltration membrane have a peak at 1647 cm -1There is one more peak at 920cm in the spectrum of FeOOH / PEI polyamide nanofiltration membrane, which is caused by the C=O of polyamide generated during interfacial polymerization, indicating that the polyamide layer was successfully synthesized on the modified FeOOH base membrane. -1 The peak of 899 cm-1 does not appear in the spectra of unmodified polyamide nanofiltration membrane and modified FeOOH-based membrane. This peak is caused by the bending vibration of Fe-OH in FeOOH. It may be due to the interaction between FeOOH / PEI and modified FeOOH-based membrane, which shifts the peak from 899 cm-1 to 920 cm-1. -1 .

[0089] Figure 4 The surface and cross-sectional SEM and AFM images of the PES base membrane, the modified FeOOH base membrane in Example 1, the FeOOH / PEI polyamide nanofiltration membrane and the unmodified polyamide nanofiltration membrane in the comparative example are shown in FIG. Figure 4 As shown, Figure a and Figure b are the surface SEM images of PES-based membrane and modified FeOOH-based membrane, respectively. It can be seen that the surface pores of the modified FeOOH-based membrane are clearly visible, and the FeOOH / PEI on the surface of the FeOOH / PEI polyamide nanofiltration membrane is evenly dispersed without aggregation; Figure c and Figure d are the surface SEM images of the unmodified polyamide nanofiltration membrane and the FeOOH / PEI polyamide nanofiltration membrane, respectively. It can be seen from Figure c that the surface of the unmodified polyamide nanofiltration membrane is a standard nodular structure. After adding FeOOH / PEI, the surface nodular structure disappears, and a network-like structure appears on the surface, which increases many cavities and is conducive to water permeability. It contributed to the increase in water flux. Figure e and figure f are cross-sectional SEM images of unmodified polyamide nanofiltration membrane and FeOOH / PEI polyamide nanofiltration membrane. It can be seen that with the addition of FeOOH / PEI, the thickness of the polyamide layer decreased from 403nm to 296nm, which is conducive to the increase in water flux. Figure g and figure h are AFM images of unmodified polyamide nanofiltration membrane and FeOOH / PEI polyamide nanofiltration membrane. With the addition of FeOOH / PEI, the surface roughness of the unmodified polyamide nanofiltration membrane increased from 7.16nm to 26nm. The increase in surface roughness can add more water channels, which is conducive to the increase in water flux.

[0090] Figure 5 The surface water contact angle diagram of FeOOH / PEI polyamide nanofiltration membrane and unmodified polyamide nanofiltration membrane is shown in Figure 5As shown in the first figure, the water contact angle of the unmodified polyamide membrane surface is reduced from 61.1 degrees to 44 degrees after adding FeOOH / PEI. As shown in the second figure, the surface is more hydrophilic. This is because the nodular structure on the surface of the polyamide membrane without adding FeOOH / PEI hinders the diffusion of water to the surrounding areas. After adding FeOOH / PEI, a uniform network structure is formed on the membrane surface with a large number of pores, which is more conducive to the diffusion of water droplets. In addition, the FeOOH / PEI polyamide nanofiltration membrane has a higher degree of cross-linking and the PA layer formed is thinner, which may also be a reason for the reduction in the water contact angle.

[0091] Figure 6 The molecular weight cut-off diagram of FeOOH / PEI polyamide nanofiltration membrane and unmodified polyamide nanofiltration membrane is shown in Figure 6 As shown in the figure, the size of the membrane pore size is expressed by the molecular weight cut-off. The retention rates of the two membranes for PEG of different molecular weights are shown in the figure. When the nanofiltration membrane has a PEG cut-off rate of 90%, it is the molecular weight cut-off of the membrane. Figure 6 It can be seen that the retention rate of PEG by unmodified polyamide nanofiltration membrane is lower than that of FeOOH / PEI polyamide nanofiltration membrane. Therefore, FeOOH / PEI polyamide nanofiltration membrane has a smaller pore structure. The results show that the molecular weight cutoff of FeOOH / PEI polyamide nanofiltration membrane is 517Da, which is lower than 580Da of unmodified polyamide nanofiltration membrane, further proving that FeOOH / PEI polyamide nanofiltration membrane has a denser PA layer.

[0092] Figure 7 The water flux and rejection rate of FeOOH / PEI polyamide nanofiltration membrane with different loading amounts are shown in Figure 2. Figure 7 As shown in the figure, the water flux of the nanofiltration membrane increased to varying degrees after the addition of FeOOH / PEI, with the largest increase at 7.5 ml. With the addition of FeOOH / PEI, the cross-linking degree of the polyamide layer on the surface of the nanofiltration membrane continued to increase, forming a denser polyamide layer. Therefore, the subsequent water flux will decrease slightly, and the salt retention rate will increase slightly with the increase of FeOOH / PEI because a defect-free polyamide layer is formed on the surface. In general, the addition of FeOOH / PEI increases the water flux of the nanofiltration membrane from 13.58 L / m 2 ·h increased to 19.89L / m 2 h, the interception rate increased from 90.78% to 94.3%.

[0093] Figure 8 The figure shows the effect of different material concentrations on the performance of FeOOH / PEI polyamide nanofiltration membrane. Figure 8 As shown in the figure, with the increase of Na2SO4 solution concentration, the water flux of FeOOH / PEI polyamide nanofiltration membrane gradually decreased, and the rejection rate remained stable.

[0094] Fig. 9 This is the long-term operation diagram of FeOOH / PEI polyamide nanofiltration membrane, such as Fig. 9 As shown in the figure, the FeOOH / PEI polyamide nanofiltration membrane still maintains high water flux and retention rate after 24 hours of long-term operation, indicating that the FeOOH / PEI polyamide nanofiltration membrane has high stability and is not easy to fall off.

[0095] Fig.10 The effect of acid-resistant treatment on FeOOH / PEI polyamide nanofiltration membrane is shown in Figure 2. Fig.10 As shown in the figure, after the FeOOH / PEI polyamide nanofiltration membrane was treated with acid, the water flux increased slightly and the retention rate decreased slightly, indicating that the FeOOH / PEI polyamide nanofiltration membrane has good acid resistance.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyamide nanofiltration membrane loaded with modified ferric oxyhydroxide, characterized in that It proceeds as follows:

1. Preparation of iron oxyhydroxide functionalized with silane coupling agent: 0.5 g of oxyhydroxide was added to 50 ml of ethanol aqueous solution, and then magnetically stirred after ultrasonic dispersion. Then 1 mL of silane coupling agent was added and reacted at 40° C. for 2 h. After centrifugation, washing and drying, silane coupling agent-functionalized oxyhydroxide was obtained.

2. Preparation of polyethyleneimine-modified iron oxyhydroxide: 0.2 g of the silane coupling agent functionalized iron oxyhydroxide was added to 50 mL of anhydrous methanol, and then ultrasonically dispersed and magnetically stirred. Then 2 g of polyethyleneimine was added, and the temperature was raised to 90° C., refluxed for 6 h, and naturally cooled to room temperature. After centrifugation, washing and drying, polyethyleneimine-modified iron oxyhydroxide was obtained, which was recorded as FeOOH / PEI.

3. Preparation of modified iron oxyhydroxide-based membrane: 3.0 mg of the above FeOOH / PEI was added to 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a modified FeOOH suspension, and then the suspension was filtered from 0 mL to 10 mL through a PES bottom membrane with a diameter of 4.0 cm, and after drying and washing, a modified FeOOH base membrane was obtained; 4. Preparation of modified FeOOH nanofiltration membrane: In a fume hood, the modified FeOOH-based membrane is horizontally spread on a glass plate with a smooth surface, and then a membrane frame is placed opposite to the center of the modified FeOOH-based membrane, and the four sides are fixed with iron clips; the piperazine aqueous solution is poured into the membrane frame, and the remaining solution in the membrane frame is poured out and drained after 90 seconds, and after drying for 10 to 20 minutes, a trimesoyl chloride-n-hexane solution is poured in, and the remaining solution in the membrane frame is poured out after 40 seconds, and then 5 mL of n-hexane solution is poured in and shaken for 30 seconds, and then the glass plate is vertically dried until the membrane surface is completely dry, the iron clip is removed and the membrane frame is taken down, and the membrane is removed from the glass plate with tweezers and marked, and then placed in a forced air drying oven, and thermally cross-linked at 60° C. for 30 minutes to obtain a modified oxyhydroxide iron-loaded polyamide nanofiltration membrane, thereby completing the preparation method.

2. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that Synthesis of oxyhydroxide in step 1: Add 2.16 g of FeCl3·6H2O and 20 mL of ethylenediamine to 40 ml of deionized water, stir for 20 min, transfer and seal in a high-temperature reaction kettle, keep warm at 85°C for 12 h, then cool to room temperature, centrifuge and wash, and vacuum dry at 80°C to obtain oxyhydroxide.

3. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that The magnetic stirring after ultrasonic dispersion in step 1 is: ultrasonic dispersion for 30 minutes and then magnetic stirring for 30 minutes.

4. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that The silane coupling agent described in step 1: KH560.

5. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that Centrifugation, washing and drying in step 1: centrifugation at a speed of 4000 r / min for 5 minutes, then washing with anhydrous ethanol for 2 to 3 times, and then vacuum drying at 40° C. for 24 hours.

6. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that The magnetic stirring after the ultrasonic dispersion in step 2: ultrasonic dispersion for 10 minutes and magnetic stirring for 30 minutes.

7. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that The centrifugation, washing and drying in step 2 are as follows: centrifugation at a speed of 4000 r / min for 5 minutes, then washing with deionized water and anhydrous methanol for 2 to 3 times respectively, and then drying at 60° C. for 24 hours.

8. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that Drying and washing in step 3: Dry in a 60°C oven for 3 minutes, and then rinse with deionized water 2 to 3 times.

9. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that The amount of the piperazine aqueous solution in step 4 is 5 mL, and the concentration is 0.5% / wv.

10. The method for preparing a modified iron oxyhydroxide-loaded polyamide nanofiltration membrane according to claim 1, characterized in that The amount of trimesoyl chloride-n-hexane solution used in step 4 is 5 mL, and the concentration is 0.1% / wv.

Citation Information

Patent Citations

  • Preparation method for polyamide composite nanofiltration membrane containing amino-modified nanoparticles

    CN107583469A

  • Two-dimensional material MXene modified polypiperazine amide nanofiltration membrane and preparation method thereof

    CN113117524A

  • Preparation method of pressure-resistant high-flux polyvinylidene fluoride nanofiltration membrane

    CN117563428A

  • Composite membrane, preparation method therefor and application thereof

    WO2020177274A1